Pcs simplified - Marmel, Elaine J. (Visual read less-learn more, 2011)
Presents introductory information about personal computers, discussing the basics of Windows 7 and covering such topics as how to use e-mail, manage files and folders, access the Internet, create documents, play digital audio, and perform computer maintenance